Using cloud computing to develop teaching self-learning competencies among the faculty members at Jouf University - S. M. Alanazy (Образование и наука)
Introduction. Cloud computing is a new model of computing based on network technology where computer-related technologies are provided as services that are permanently available for use. This technology saves faculty members’ time, and increases their interaction and communication with colleagues and students. Moreover, cloud computing solutions help faculty members finish and follow up all the required courses, in addition to allowing the faculty members to store and retrieve information comprehensively and immediately. As a result, using cloud computing provides practical, interactive solutions to deal with the academic tasks which a faculty member needs to perform his/her current academic work.Aim. The current study aimed to uncover the reality of using cloud computing to develop the teaching competencies.Methodology and research methods. The study relied on applying the survey method based on a descriptive approach using two types of questionnaire as the main tools for data collection. The sample of the study includes 48 faculty members and 103 students from the College of Education at Jouf University.Results and scientific novelty. The results showed that self-assessment of using cloud computing to develop self-learning teaching competencies among faculty members is of a high level, while the teaching competencies for the application of cloud computing in self-directed learning among faculty members are of an average level according to their students. The results also demonstrated no significant relationship between these two main types of assessment.Practical significance. The current study is significant in light of the fact that it facilitates to understand the impact of utilising cloud computing to accomplish proficient and educational abilities for faculty members at Jouf University.